(3egPH GdSff GdocHQi ddHjgbjs - (3eMeO Hf CMeO Hf YKeGf Hf bGjeGR GdPgHj, TeS GdOjf, CHh YHO Gddg,J (B748 (3g` s; (3CHh HcQ eMeO GdHjgbjs
(3ChdgG (B:s
(3Ef Gdfgj Yf GdUdGI hbJ WdhY GdTeS hhbJ ZQhHgG bO NU efg HYV GdCecfI s
(3BNQgG (B:s
(3HGH ef CMQe HGdYeQI ef GdJfSje , ef cJGH GdML s
(3ef GdfSNI faSgG fbdkG Yf NW GdeDdas
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3JgPjHs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs